Oral health condition among tobacco users and non users attending the Outpatient Department of Pioneer Dental College (Bangladesh Journal of Dental Research & Education, 2013)
Bangladesh Journal of Dental Research & Education, Vol. 01, No. 01, January 2011, Page 8-11 DOI: http://dx.doi.org/10.3329/bjdre.v1i1.15794